A3_3 The Solar Chair? - Ruston, Ryan; Sirovica, Slobodan; May, Christopher; Smith, Timothy (Physics Special Topics, 2011)
This journal explores the feasibility of using solar energy to execute prisoners on death row. The concept is shown to be possible, results showing a requirement of 86 solar panels of high efficiency to execute one prisoner. The economic practicalities of using solar energy for this purpose are also scrutinised.